Evaluation of the biochemical methane potential of residual organic fraction and mechanically-biologically treated organic outputs intended for landfilling. (15th July 2020) - Carchesio, Manuela; Di Addario, Martina; Tatàno, Fabio; de Rosa, Sandro; Gambioli, Alma
Graphical abstract: Highlights: A mechanically separated residual organic fraction (ms-OFRMW) was investigated. A biostabilised residual organic fraction (bios-OFRMW) was investigated. A biodried residual fine fraction (biod-FFRMW) was investigated. ms-OFRMW could be suitable for bioenergy recovery through anaerobic digestion. bios-OFRMW and biod-FFRMW may still contribute to landfill methane generation. Abstract: Mechanical biological treatment (MBT) approaches are being adopted to manage residual municipal waste (RMW) to promote the prevention or reduction of potential environmental impacts of landfilling. From this perspective, the present study aimed to increase the knowledge of the biological (anaerobic) stability of different MBT organic outputs and, conversely, initial methane generation from residual organic waste. Biochemical methane potential (BMP) tests, along with initial and final characterisations of substrates and digestates, were conducted on: a mechanically separated organic fraction from RMW (ms-OFRMW); a first MBT organic output represented by a biostabilised organic fraction from RMW (bios-OFRMW); and a different MBT organic output represented by a biodried fine fraction from RMW (biod-FFRMW). The ms-OFRMW had a BMP of 445.6 Nml CH4 g VS −1, which was comparable or even higher than those from separately collected and source-sorted organic fractions. The fibre and liquor fractions of the digestate from ms-OFRMW with inoculum showed potential profiles of P-rich amendment and N-rich fluid phase, respectively, even satisfying environmental limits (with the exclusion only of Cu and Zn contents in fibre fraction that, however, remained within typical ranges for agricultural digestates). The BMPs for bios-OFRMW and biod-FFRMW were 143.4 and 261.0 Nml CH4 g VS −1, respectively, indicating that these streams may still contribute to landfill methane generation. The BMPs for bios-OFRMW, biod-FFRMW, and ms-OFRMW were positively associated with the degrees of conversion of the substrates (17, 32, and 55%, respectively) and the potential dynamic respiration indexes (955, 3126, and 6062 mg O2 kg VS −1 h −1, respectively).